Two-pore channel regulators: who is in control? - Deutsch, Rebecca; Kudrina, Veronika; Freichel, Marc; Grimm, Christian (Frontiers in physiology, 2025)
Two-pore channels (TPCs) are adenine nucleotide and phosphoinositide regulated cation channels. NAADP activates and ATP blocks TPCs, while the endolysosomal phosphoinositide PI(3,5)P2 activates TPCs. TPCs are ubiquitously expressed including expression in the innate as well as the adaptive immune system. In the immune system TPCs are found, e.g. in macrophages, mast cells and T cells. In cytotoxic T cells, NAADP activates TPCs on cytolytic granules to stimulate exocytosis and killing. TPC inhibition or knockdown increases the number of regulator T cells in a transmembrane TNF/TNFR2 dependent manner, contributing to anti-inflammatory effects in a murine colitis model. TPC1 regulates exocytosis in mast cells in vivo and ex vivo, and TPC1 deficiency in mast cells augments systemic anaphylaxis in mice. In bone marrow derived macrophages NAADP regulates TPCs to control phagocytosis in a calcineurin/dynamin dependent manner, which was recently challenged by data, claiming no effect of TPCs on phagocytosis in macrophages but instead a role in phagosome resolution, a process thought to be mediated by vesiculation and tubulation. In this review we will discuss evidence and recent findings on the different roles of TPCs in immune cell function as well as evidence for adenine nucleotides being involved in these processes. Since the adenine nucleotide effects (NAADP, ATP) are mediated by auxiliary proteins, respectively, another major focus will be on the complex network of TPC regulatory proteins that have been discovered recently.